The repercussions of the Lockerbie incident, on the fall of the Muammar Gaddafi regime in 2011 - Arshad Hamza Hassan / Wael Jabber Jouda Al-Nadawy ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2022)
The research included several axes, the first focused on the roots of the US administration’s relations with Libya until 1988 and discussed the historical background of those relations, in order for the reader to understand the dimensions of the US administration’s policy in Libya, while the second axis continued the internationalization of the Lockerbie case in the UN Security Council, and the role of the International Court of Justice In managing discussions and disputes between the two countries on the Lockerbie issue, and the third axis focused on the issue of Libya after the Lockerbie incident until 1998, and the fourth axis reviewed the reasons for the US administration to overthrow the Muammar Gaddafi regime in 2011. The research relied on a variety of sources and references according to the requirements of the research topic.